Electron-phonon scattering in graded quantum dots - Diniz, G. S. (2010)
Theoretical calculations of electron-phonon scattering rates in GaAs/AlxGa1¡xAs spherical quantum dots have been performed by means of effective mass approximation in the frame of finite element method. The influence of a roughness interface and external magnetic fields are analysed for different scattering rate transition. Our results open interesting channels for electron dephasing times manipulation. Keywords: Theoretical calculations; Electron-phonon scattering; GaAs/AlxGa1¡xAs